Neck/shoulder discomfort due to visually demanding experimental near work is influenced by previous neck pain, task duration, astigmatism, internal eye discomfort and accommodation. - Camilla Zetterberg; Mikael Forsman; Hans O Richter (PLoS ONE, 2017)
Visually demanding near work can cause eye discomfort, and eye and neck/shoulder discomfort during, e.g., computer work are associated. To investigate direct effects of experimental near work on eye and neck/shoulder discomfort, 33 individuals with chronic neck pain and 33 healthy control subjects performed a visual task four times using four different trial lenses (referred to as four different viewing conditions), and they rated eye and neck/shoulder discomfort at baseline and after each task. Since symptoms of eye discomfort may differ depending on the underlying cause, two categories were used; internal eye discomfort, such as ache and strain, that may be caused by accommodative or vergence stress; and external eye discomfort, such as burning and smarting, that may be caused by dry-eye disorders. The cumulative performance time (reflected in the temporal order of the tasks), astigmatism, accommodation response and concurrent symptoms of internal eye discomfort all aggravated neck/shoulder discomfort, but there was no significant effect of external eye discomfort. There was also an interaction effect between the temporal order and internal eye discomfort: participants with a greater mean increase in internal eye discomfort also developed more neck/shoulder discomfort with time. Since moderate musculoskeletal symptoms are a risk factor for more severe symptoms, it is important to ensure a good visual environment in occupations involving visually demanding near work.